Grammar : - Broukal, Milada (McGraw-Hill, 2005)
The passive voice, causatives, and phrasal verbs, gerunds and infinitives, agreement and paralel structure, noun clause and reported speech, adjective clauses, adverb clauses, conditional sentences.